Sentiment Analysis Before Presidential Election 2024 Using Naïve Bayes Classifier Based On Public Opinion In Twitter: Analisa Sentimen Jelang Pilpres 2024 Menggunakan Naïve Bayes Classifier Berdasarkan Opini Publik Di Twitter - Prasetyo, Heri; Fitrani, Arif Senja (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the performance of the Naïve Bayes Classifier algorithm and sentiment analysis tested on a dataset obtained from Twitter social media scrapping with the topic of 2024 presidential candidates. Three candidates frequently discussed in public spaces were used as keyword parameters in data mining: #anis, #ganjar, and #pilpres2024, resulting in 3021 tweets extracted from 12/1/2022 to 31/1/2023, which were successfully converted to